The two roads from passion to sport performance and psychological well-being: The mediating role of need satisfaction, deliberate practice, and achievement goals. (May 2017) - Verner-Filion, Jérémie; Vallerand, Robert J.; Amiot, Catherine E.; Mocanu, Irina
Abstract: Objectives: Research on passion has demonstrated the existence of two roads toward sports performance through the effects of deliberate practice (Vallerand et al., 2007, 2008). The first emanates from harmonious passion (HP) and contributes to both performance and psychological well-being. The second stems from obsessive passion (OP), and performance comes at the cost of well-being. The present research proposes that need satisfaction (Deci & Ryan, 2000) mediates the relation of HP, but not OP, with both outcomes. In Study 2, achievement goals were added to the model. Mastery goals were expected to mediate the positive relation between HP and outcomes, whereas performance-avoidance goals would be associated with OP and, thus be detrimental to athletes. Design: Two studies using correlational (Study 1) and longitudinal (Study 2) designs. Method: Study 1 ( N = 172) was conducted with soccer players. Study 2 was conducted with hockey players ( N = 598). Athletes completed measures of passion, need satisfaction, life satisfaction, deliberate practice, and achievement goals (Study 2 only). Coaches assessed performance in Study 1. Study 2 used games played in competitive leagues over 15 years to measure performance. Results: Analyses using SEM provided support for the mediating role of need satisfaction (Study 1 and 2) and achievement goals (Study 2) in the relation of HP with outcomes. In contrast, deliberate practice (Study 1 and 2) meditated the relation between OP and performance. Conclusions: This research supported the mediating role of need satisfaction in the 'two roads to performance" (Vallerand et al., 2007, 2008). Highlights: The role of basic needs in the "two roads to performance" (Vallerand et al., 2007; 2008) is examined. Performance is assessed at short (Study 1) and long term (i.e., 15 years, Study 2). Basic needs mediate the relation of HP with life satisfaction, deliberate practice, and performance. The relation between OP and performance is only mediated by deliberate practice. The mediating role of achievement goals in long-term performance (Study 2) is also examined.